Declining Cogging Torque Technique of an Integral Slot Number for Permanent Magnet Machines - Herlina Herlina; Tajuddin Nur; Maria Angela Kartawidjaja; Linda Wijayanti; Kumala Indriati; Sheila Tobing (Universitas Syiah Kuala, 2023)
The existence of cogging torque in electric equipment has been considered undesirable. This kind of friction in the air-gap impacts the alignment of flux and the stator slots, resulting in the observed outcome. Consequently, the imposition of restrictions on the rotation of the rotor is employed to generate electrical energy. This research endeavor primarily aims to mitigate the cogging torque of electrical machinery. The current utilization involves employing a total of 3 permanent magnet synchronous machines, often known as inset PMMs, which possess a slot count of 24 and a pole count of 8. The employed technique involves the integration of an optimal pole arc method in conjunction with the implementation of slots cut into the magnet's edge. The machine model under investigation has two fundamental variants, namely Models 1 and 2. These models are equipped with 1one-step slotted (OSS) and 2two-step slotted (TSS) edges on each magnet, in addition to pole arc optimization. The simulation was conducted using the Finite Element Method Magnetics (FEMM) 4.2 software together with LUA scripts, with a focus on rotor rotation ranges of 1 degree. Model 2 exhibited a decrease in cogging torque of 0.01 Nm, whereas Model 1 demonstrated a reduction of 0.015 Nm, and the basic model had a decrease of 0.02 Nm. When implementing a dual-layered cutting edge on a magnet and attempting to optimize its pole arc, it is imperative to consider that the cogging torque's peak magnitude becomes substantially diminished or entirely eliminated.